Embodied Oscillative Ethics: A Framework for Participatory Ethics in Body Mapping Research - Mikaela Linell; Dalia Abdelhady (International Journal of Qualitative Methods)
This article presents an innovative participatory approach to the ethical aspects of conducting body mapping research. Drawing from experiences from an earlier project with digital sex workers, we examine how body mapping, when integrated with what we term “embodied oscillative ethics,” creates opportunities for meaningful collaboration and knowledge co-creation while addressing complex ethical challenges. We demonstrate how this creative methodology enables participants to become active knowledge producers rather than passive research subjects. The approach recognizes participants as experts of their own experiences while acknowledging the situated vulnerabilities they navigate. Embodied oscillative ethics highlights how ethical considerations should transcend the research design and bridge into the data collection process in a participatory way. Our findings reveal how body mapping’s creative and embodied dimensions, and the approach we suggest to complement it, facilitate participant empowerment and transformative dialogue. While body mapping helps explore embodied dimensions of digital interaction, the embodied oscillative ethics framework additionally ensures ethical practice through continuous attention to participant agency and consent. We also reflect critically on the researchers’ own vulnerabilities and positionalities when conducting sensitive research. This methodological innovation offers valuable insights for researchers studying topics that are difficult to approach, demonstrating how creative approaches can unveil alternative knowledge.